2002
DOI: 10.2746/042516402776767187
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and characterisation of primary and subcultured equine keratinocytes

Abstract: Summary We describe the establishment and characterisation of equine keratinocyte cultures with maintenance of a high proliferative capacity up to the second passage. Improved attachment and growth were obtained by seeding primary cells on equine feeder layers. Subcultured keratinocytes showed optimal growth when seeded on collagen type I. The proliferation rate of cells on this substrate exceeded that seen for cells seeded on equine feeder layers. By immunohistochemistry, epithelial origin and state of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
(37 reference statements)
3
30
1
Order By: Relevance
“…We found all lamellar cells expressed vimentin in the cell cytoplasm regardless of the calcium concentration and did not display a fibroblastic cell morphology. Additionally, vimentin expression may be cell origin specific, as equine skin keratinocytes have been found to not express vimentin in culture [16] while lamellar keratinocytes in culture have been shown to express vimentin [14] in agreement with findings in this work.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We found all lamellar cells expressed vimentin in the cell cytoplasm regardless of the calcium concentration and did not display a fibroblastic cell morphology. Additionally, vimentin expression may be cell origin specific, as equine skin keratinocytes have been found to not express vimentin in culture [16] while lamellar keratinocytes in culture have been shown to express vimentin [14] in agreement with findings in this work.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to another report [16], skin keratinocytes isolated from lip epithelium were found to proliferate and propagate in culture. In the present study, cells were found to adhere well to collagen type I during the initial isolation and this substrate was used for initial growth in addition to subculture.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations